2005
DOI: 10.1007/s10047-005-0317-9
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of an ATS valve in the aortic position: the first reported case caused by pannus formation

Abstract: A 64-year-old woman underwent aortic valve replacement with a 21-mm Advancing The Standard (ATS) open-pivot mechanical heart valve for bicuspid aortic valve stenosis. In addition to the appearance of a new cardiac murmur, echocardiography performed 3 years after surgery showed a high pressure gradient across the ATS valve and a reduction in the valve orifice area. Cineradiography of the valve revealed restricted leaflet opening. Subsequent multidetector-row computed tomography clearly demonstrated pannus overg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…Our study vs. existing literature Until now, there have been only some scattered case reports or case series in the literature on the use of MDCT to diagnose prosthetic valve dysfunction [12][13][14][15][16][17]. Although these studies reported encouraging images and diagnostic results, they may have been confounded by a severe selection bias due to the inherent limitation of the article format.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Our study vs. existing literature Until now, there have been only some scattered case reports or case series in the literature on the use of MDCT to diagnose prosthetic valve dysfunction [12][13][14][15][16][17]. Although these studies reported encouraging images and diagnostic results, they may have been confounded by a severe selection bias due to the inherent limitation of the article format.…”
Section: Discussionmentioning
confidence: 62%
“…Pannus formation was defined according to previous case reports [13,16,17] and our clinical experience as a small low-density region located at the inflow side of the prosthetic valve suture ring. Care was taken to exclude the beam-hardening artifact, which was defined as a black shining line projecting outwards from the dense portion of the device (Fig.…”
Section: Mdct Of Prosthetic Heart Valvesmentioning
confidence: 99%
See 1 more Smart Citation
“…CT images can also help visualize the morphology and motion of native and diseased stenotic aortic valves and precisely measure aortic valve opening areas. Several studies [39][40][41][42][43][44][45] suggest that multidetector CT can help assess mechanism of dysfunction in mechanical prosthetic heart valve disorders.…”
Section: Discussionmentioning
confidence: 99%
“…15 Over the past 5 years, a few case reports [16][17][18][19] and research studies [20][21][22][23][24][25][26][27][28] with limited number of patients have been published regarding the use of multidetector computed tomography (MDCT) for the 2…”
Section: See Editorial By Bonnichsen and Pellikka See Clinical Perspementioning
confidence: 99%